Status of Vitamin D among Patients Attending Internal Medicine Department in a Tertiary Care Centre of Rural Nepal: A Hospital Based Cross-Sectional Study - Giri, Rajendra Mani; Joshi, Sanjeev; Panti, Ram Chandra; Gautam, Sanjeev; Joshi, Kushal Raj; Sharma, Sandip Kumar; Rokaya, Manish; Thapaliya, Pooja (Journal of National Heart and Lung Society Nepal, 2024)
Background: Vitamin D deficiency is a pandemic with global prevalence estimated to be 47.9%. Many factors like sunlight exposure, seasonal and geographic variability affect vitamin D levels. This study, conducted in a high altitude location of the mountainous region of western Nepal helps to identify prevalence and associated factors of vitamin D deficiency. Methods: This was a hospital based observational, cross sectional study done on 372 patients attending internal medicine outpatient department of Karnali Academy of Health Sciences, Jumla during June to September 2025. Serum vitamin D levels were assessed and the distribution of vitamin D levels with age, sex, ethnicity, occupation and education studied. Vitamin D levels were characterised as 5(OH)D concentration 50nmol/L or 20ng/ml as vitamin D deficiency, serum 25(OH)D levels of 51-74 nmol/L or 21-29ng/ml as insufficiency, and levels ≥30 ng/ml as sufficient. Results: Prevalence of vitamin D deficiency was 34% and insufficiency was 43%. The prevalence of vitamin D deficiency was significantly higher among females (38%, compared to 26% in males), those with indoor activity (53%) and those with university education (53%). There was no difference in vitamin D levels between age or ethnicity. Conclusion: Overall 77% had inadequate vitamin D levels. Most affected groups were female, those with indoor activity and those with university education.